Instagram Based Arabic Vocabulary Learning among First Year Students - Mega Satria Nurul Falah; Awaliyah Ainun Niswah (AT-TA'LIM, 2026)
This study aims to explore how first-year students experience and engage in Arabic vocabulary learning through Instagram at an International Open University. Using a qualitative descriptive–exploratory design, the study focuses on students lived learning experiences rather than merely examining learning outcomes or media effectiveness. Data were collected through semi-structured in-depth interviews with ten first-semester students and complemented by observations of their Instagram learning activities. The data were analyzed using thematic analysis to identify patterns of perception, engagement, and meaning construction in students’ learning experiences. The findings reveal three interrelated dimensions of Instagram-based vocabulary learning. First, students perceive Instagram as a contextual and relevant learning space that provides practical vocabulary connected to everyday communication. Second, the learning process is experienced as light, visual, and motivating due to the platform’s multimodal content, which facilitates comprehension and reduces learning pressure. Third, students demonstrate selective and autonomous participation, primarily by viewing and saving posts rather than actively interacting. The study highlights that meaningful digital vocabulary learning is shaped not only by platform features but also by contextual relevance, affective experience, and learner autonomy, positioning Instagram as a complementary informal learning space that supports formal Arabic language instruction in higher education